DIGITAL LEADERSHIP AS A GROWTH ENGINE IN SMES: BRIDGING CAPABILITY, SELF-EFFICACY, AND ENTREPRENEURIAL PERFORMANCE - Novi Handayani; Wahyu Eko Pujianto (POLITEKNIK LP3I JAKARTA, 2025)
Entrepreneurial performance has an important role in determining the sustainability and growth of SMEs. This study aims to analyze the effect of digital leadership on entrepreneurial performance with the mediating role of digital capability and self-efficacy as moderation. The research was conducted on small and medium enterprises (SMEs) in Sidoarjo and Pasuruan, involving 200 respondents from shop heads, managers, and decision-makers. The sampling technique used cluster sampling to group samples from a population distributed in two regions. Data analysis was carried out using quantitative methods, such as conducting item validity and reliability tests and testing hypotheses with SEM-PLS version 4.0. The results showed that digital leadership has a significant effect on entrepreneurial performance. Digital capability mediates the relationship between digital leadership and entrepreneurial performance. However, self-efficacy weakens the relationship between digital leadership and entrepreneurial performance, showing a negative moderation effect. This study confirms the importance of digital leadership and digital capability in improving the performance of SMEs while providing insights for business people to manage self-efficacy proportionally.